Interaction between ambient pollutant exposure, CD14 (-159) polymorphism and respiratory outcomes among children in Kwazulu-Natal, Durban. (March 2017) - Makamure, MT; Reddy, P; Chuturgoon, A; Naidoo, RN; Mentz, G; Batterman, S; Robins, TG
The objective of this study was to determine if the association between exposure to ambient air pollutants such as sulfur dioxide, nitrogen dioxde (NO2 ), nitrous oxide (NO), and PM10, and variation in lung function measures was modified by genotype. A validated questionnaire was administered to 71 African children to evaluate prevalence of respiratory symptoms. Atopy was evaluated by skin-prick testing and bihourly measures of lung function (spirometry) were collected. Gaseous air pollutant concentrations were monitored continuously. CD14 polymorphism was genotyped and plasma CD14 levels were measured. There was no statistically significant association between the CD14 (159) CT+TT polymorphism with any asthma-related phenotype. There was a significant association between lung function (forced expiratory volume in 1 second intraday variability) and NO2 and NO among participants carrying the CD14 CT/TT genotype for lags 1, 2, and the 5-day average. Similarly, statistically significant gene–pollutant interactions ( p < 0.05) were found with NO and CD14 CT/TT at lag 2 and for the 5-day average. While there was no association with any respiratory phenotype (as determined by symptoms), the CD14 CT/TT genotype appeared to be protective to increased exposure to NO2 and NO.